2012
DOI: 10.1111/j.1529-8027.2012.00407.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and serological features of acute sensory ataxic neuropathy with antiganglioside antibodies

Abstract: There is as yet no consensus for considering pure acute sensory ataxic neuropathy (ASAN) as a variant of Guillain-Barré syndrome (GBS). Reactivity against gangliosides sharing disialosyl epitopes has been reported in these patients. The aim of this study was to determine the spectrum of reactivity against gangliosides in ASAN and to define the clinical pattern. From our database we identified patients with suspicion of ASAN. We defined ASAN as the presence of ataxia of peripheral origin with loss of propriocep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…In the past, ASAN was not considered to be a GBS variant because affected patients do not meet the diagnostic criteria for sensory GBS and lack demyelinating features on electrodiagnostic studies. Both ASAN and ataxic GBS, however, share many features with MFS including acute ataxia, areflexia, antecedent infection, and antiganglioside antibodies but lack the typical ophthalmoplegia 110112. The presence of a Romberg sign helps differentiate ASAN from ataxic GBS.…”
Section: Differential Diagnosis Of Sensory Ataxiamentioning
confidence: 99%
See 2 more Smart Citations
“…In the past, ASAN was not considered to be a GBS variant because affected patients do not meet the diagnostic criteria for sensory GBS and lack demyelinating features on electrodiagnostic studies. Both ASAN and ataxic GBS, however, share many features with MFS including acute ataxia, areflexia, antecedent infection, and antiganglioside antibodies but lack the typical ophthalmoplegia 110112. The presence of a Romberg sign helps differentiate ASAN from ataxic GBS.…”
Section: Differential Diagnosis Of Sensory Ataxiamentioning
confidence: 99%
“…Patients with ASAN may harbor anti-disialosyl antibodies to GD1b alone or in combination with antibodies to CD3, GQ1b, or GT1a. Autoantibodies against gangliosides without disialosyl epitopes (GD1a and GM3) may also be present 112. Given that patients with ASAN typically have an antecedent infection, monophasic course, and excellent recovery, they should be considered under the rubric of GBS, in the subcategory of acute ataxic neuropathy 112.…”
Section: Differential Diagnosis Of Sensory Ataxiamentioning
confidence: 99%
See 1 more Smart Citation
“…In 1994, a study reported a patient with acute self‐limiting ataxic neuropathy who had IgG antibodies to GD1b and GD3, but not to GT1a and GQ1b . Since then, several cases with acute sensory ataxic neuropathy with IgG antibodies to GD1b alone or some of the glycolipids with at least one disialosyl residue, including GD1b, have been reported . GD1b is present in large neurons of dorsal root ganglia .…”
Section: Glycolipid Antibodies In Guillain‐barré Syndromementioning
confidence: 99%
“…32 Since then, several cases with acute sensory ataxic neuropathy with IgG antibodies to GD1b alone or some of the glycolipids with at least one disialosyl residue, including GD1b, have been reported. 33,34 GD1b is present in large neurons of dorsal root ganglia. 35 In 1996, a study reported the induction of sensory ataxic neuropathy in rabbits sensitized with GD1b.…”
Section: Humoral Immunitymentioning
confidence: 99%